DETERMINATION OF KOH EFFICIENCY AS CARBOSORB IN DETERMINING AGE OF CORAL REEF SAMPLES IN SELAYAR ISLANDS THROUGH LSC METHOD (LIQUID SCINTILLATION COUNTING) - Muhammad Amri; Alfian Noor; Maming Maming (Hasanuddin University, 2019)
Research using the method of LSC (Liquid Scintillation Carbon) in determining the age of coral reefs in the Selayar islands has been carried out. The samples of coral reefs were taken between the tides. Sample preparation was carried out physically and chemically using an acid-base mixture solution: NaOH, H2O2, HClO4 and HCl produced coral samples that looked whiter with weight reduction of up to 1.6%. Carbonate is separated into CO2 by reaction with 10% HCl and absorption with KOH 1 M as K2CO3. Total carbon is determined by the titration method which produces 0.0542 g of total carbon sample. Specific activity of 14C measured by enumeration with LSC is 12.0542 DPM/gC. The age of coral reef samples obtained from sample specific activity data was 1971,728 years